Analisis Faktor Resiko Kejadian Preeklamsia: Studi Kasus Kontrol di RSI PKU Muhammadiyah Pekajangan - Istianah, Ana; Wulandari, Rr. Catur Leny; Adyani, Kartika (Jurnal Midwifery, 2026)
Introduction: The global maternal mortality rate (MMR) has decreased to 72.9 per 100,000 live births, while in Indonesia it remains at 189 per 100,000 live births. In Central Java Province, the MMR was recorded at 62.27 per 100,000 live births. In Pekalongan Regency, the maternal mortality rate fluctuated, increasing to 27 cases in 2021 and decreasing to 18 cases in 2024. Preeclampsia is a leading cause of maternal death, increasing maternal and fetal morbidity and mortality. The high number of preeclampsia cases at RSI PKU Muhammadiyah Pekajangan prompted this study to analyze factors associated with the incidence of preeclampsia in pregnant women. Method: A quantitative analytical study with a case-control design involving 152 respondents (76 cases and 76 controls) from medical records from January–June 2025. Independent variables included maternal age, parity, history of hypertension, and obesity, while the dependent variable was the incidence of preeclampsia. Analysis used the Chi-Square and Odds Ratio tests. Result: The results of the study showed a relationship between maternal age (p=0.023; OR=0.376), history of hypertension (p=0.000), and obesity (p=0.000) with the incidence of preeclampsia. Parity was not statistically related (p=0.732), Data analysis used the Chi-Square test and Odds Ratio (OR). Conclusion: There is a significant relationship between age, history of hypertension, and obesity with the incidence of preeclampsia, while parity is not significantly related to pregnant women at RSI PKU Muhammadiyah Pekajangan